THE EFFECT OF COOLING MEDIA VARIATIONS AND CYLINDER LINER POSITION ON THE HEAT BALANCE EFFICIENCY OF THE L-300 DIESEL ENGINE - Wambrauw, Karlos; Haurissa, Jusuf (DINAMIS, 2024)
This study aims to measure the heat balance in the L300 diesel engine using different radiator coolant media and to examine the impact of changing the cylinder liner position. The method used is laboratory experimentation, including data collection and analysis. The variables studied include independent variables such as radiator temperature, dependent variables being the heat balance, and controlled variables such as engine speed, which is maintained at 1500 rpm. The testing was carried out for each cooling medium. The materials used for testing consist of three types of cooling media: radiator coolant, refillable water, and AC water, along with one L300 - 4D56 diesel engine unit. The results show that at 1500 rpm engine speed, the specific fuel consumption for the engine with the reversed cylinder liner reached 2.863 kg/HP.hour. The heat balance comprises Qf = 100%, Qe = 20%, Qef = 11%, Qcool = 29%, Qm = 20%, and Qi = 20%. Meanwhile, for the engine with the standard cylinder liner position, the specific fuel consumption was 2.0832 kg/HP.hour, with the heat balance composition of Qf = 100%, Qe = 30%, Qef = 14%, Qcool = 20%, Qm = 15%, and Qi = 21%. The heat balance percentage difference between the two engine configurations is 7%. Based on these results, the engine with the reversed cylinder liner position is still considered feasible and efficient for use.